Facial artery myomucosal free flap for cheek mucosa reconstruction: A case report. Issue 5 (24th May 2013) - Massarelli, Olindo; Gobbi, Roberta; Biglio, Andrea; Tullio, Antonio
<x xml:space="preserve">Abstract</x> Squamous cell carcinoma (SCC) of the buccal mucosa is an aggressive form of oral cancer. It tends to spread to adjacent tissues and often metastasizes to occult cervical node. There are multiple techniques for cheek reconstruction after tumor removal, including temporalis myocutaneous and temporoparietal fascial pedicled flaps and a forearm free flap. In this report, a case of a 76‐year‐old man with SCC of the left cheek mucosa and extending to the posterolateral superior alveolar ridge is presented. The patient underwent radical excision of the tumor, omolateral modified radical neck dissection (MRND‐III), and contralateral selective neck dissection (levels I–III). Reconstruction was performed with a facial artery myomucosal free flap. The flap was transplanted successfully, and there were no donor or recipient site complications. This technique is a good reconstructive option because of its adherence to the plastic surgery principle of "replacing like with like" and its minimal donor‐site morbidity. © 2013 Wiley Periodicals, Inc. Microsurgery 33:401–405, 2013.